Voices and Choices of HIV-serodiscordant Heterosexual Couples - Lelaka, Constance Matshidiso (Jurnal Multidisiplin Madani, 2024)
There is limited information regarding serodiscordancy. HIV-serodiscordant couples face challenges in their relationships, this is likely to threaten their relationship’s and they need psychosocial support from various sources to strengthen their quality of life and well-being. The study seeks to explore the voices and choices from HIV-serodiscordant heterosexual couples. This was a qualitative study, and thirteen (13) participants were purposively sampled. Data was collected using semi-structure interview guide and all interviews were held face-to-face at the hospital with participants and data was thematically analysed. The main overarching themes emerged from the qualitative included the following:  perceptions regarding the limited knowledge on discordant couples, the importance of providing psychosocial to discordant couples, challenges facing discordant couples in relationships, and couple’s sexual and reproductive needs. The results suggests that there is limited knowledge and education on discordancy. There is need for discordant couple’s services and programmes that should be streamed lined to provide comprehensive and sufficient psychosocial support, mitigate challenges faced by discordant couples and promote couples sexual and reproductive health via the safer conception services ensuring reduction of HIV risk practices behaviours among the couples